Metopic and sagittal synostosis in Greig cephalopolysyndactyly syndrome: five cases with intragenic mutations or complete deletions of GLI3. - Hurst, J; Jenkins, D; Vasudevan, P; Kirchhoff, M; Skovby, F; Rieubland, C; Gallati, S; Rittinger, O; Kroisel, P; Johnson, D; Biesecker, L; Wilkie, A (2011)
Greig cephalopolysyndactyly syndrome (GCPS) is a multiple congenital malformation characterised by limb and craniofacial anomalies, caused by heterozygous mutation or deletion of GLI3. We report four boys and a girl who were presented with trigonocephaly due to metopic synostosis, in association with pre- and post-axial polydactyly and cutaneous syndactyly of hands and feet. Two cases had additional sagittal synostosis. None had a family history of similar features. In all five children, the diagnosis of GCPS was confirmed by molecular analysis of GLI3 (two had intragenic mutations and three had complete gene deletions detected on array comparative genomic hybridisation), thus highlighting the importance of trigonocephaly or overt metopic or sagittal synostosis as a distinct presenting feature of GCPS. These observations confirm and extend a recently proposed association of intragenic GLI3 mutations with metopic synostosis; moreover, the three individuals with complete deletion of GLI3 were previously considered to have Carpenter syndrome, highlighting an important source of diagnostic confusion.